A methodology for estimating the ammonia emission from crop residues at a national scale. (April 2019) - de Ruijter, F.J.; Huijsmans, J.F.M.
Abstract: Crops and crop residues contribute to pollution of the environment by ammonia (NH3 ) volatilization. This study focusses on the volatilization from crop residues, defined as residues after a management action or frost i.e. residues that are left on the field after harvest, after killing by use of herbicides or after frost. The objective of this study was to develop a general methodology to calculate the volatilization from crop residues and to estimate their contribution to the NH3 volatilization at a national scale. A regression model was developed to assess the NH3 volatilization from crop residue based on the nitrogen (N) content of the residue (emission factor). Information on farm practices (degree of incorporation of residues, the application of crop killing and mowing frequency of grass), harvested crop areas, and N load in crop was used to calculate the emission from crop residues at national scale. The contribution of crop residues to the national NH3 volatilization in the Netherlands was substantial and calculated at 1.9 million kg NH3 -N. Grassland contributed about three quarters of total NH3 volatilization from crop residues. Most volatilization occurs from the mowing losses (54%) and renovation of grassland (14%). Residues of arable crops also have a contribution of 14% to total volatilization. Within arable crops, potatoes are responsible for more than half of the NH3 volatilization, with the largest contribution from seed potatoes, followed by sugar beet and cabbage crops. NH3 volatilization from green manure crop residues (killed by freezing or spraying herbicides) is about half the volatilization from arable crop residues (7%). The developed general approach for estimating the NH3 volatilization from crop residues was applied for the Netherlands but may also be applicable to other countries, taking into account their site specific emission factors and farm practices statistics. Highlights: Crop residues can have a substantial contribution to national ammonia emission. A novel and simple model is presented to estimate the contribution from crop residues. The model can be applied in other temperate regions using local cropping statistics. The N content of residues has a large effect on calculated ammonia volatilization. Crop residues from intensively managed grassland have a relatively high contribution.